A study of sleep quality and occupational fatigue among healthcare providers who work shift duty in emergency department, Hospital Universiti Sains Malaysia in the year 2014 - Hoon, Teo Chiang (2016)
Health care workers generally are under tremendous stress. This is especially true in the emergency department where the Emergency Medical Services (EMS) workers are constantly under significant pressure with regard to health care and responsibilities. Healthcare providers in Emergency Department are required to deliver critical around-the-clock or “24/7” operational care to a variety of patients. The emergency department (ED) presents a real risk factor for cases of burnout because it generates more stress than any other department (O. Fernández Martínez and García, 2007). This is evidenced by increased pressure on health care, patients demanding a reduction in waiting time, long working hours, few breaks and a lack of cooperation from patients and their families. EMS workers are constantly and increasingly faced with difficult clinical cases and workloads that are taxing physically, mentally and emotionally. There are also lots of civil and legal responsibility associated with medical work, residents are frequently at risk and in potentially dangerous situations, constantly feeling rushed and harassed (O. Fernández Martínez and García, 2007).Providing quality health care services requires EMS providers to attend to details critical for life, such as monitoring of changing vital signs, administering the correct type and dose of medications, and in general, making crucial decisions to achieve optimal patient care. They are regularly required to problem-solve delicate and complex issues, inan independent, self-governing and timely fashion. They are also required to perform clinical skills, procedures and driving with professionalism and care. Their management is crucial during treatment of critical patients, where skills are paramount and errors in judgment or lapses in concentration could end up having fatal consequences (Frank Archer, 2012).